Cardiovascular magnetic resonance reference ranges for the heart and aorta in Chinese at 3T. Issue 1 (December 2016) - Le, Thu-Thao; Tan, Ru; De Deyn, Michelle; Goh, Elizabeth; Han, Yiying; Leong, Bao Ru; Cook, Stuart Alexander; Chin, Calvin
Abstract Background Cardiovascular magnetic resonance (CMR) reference ranges have not been well established in Chinese. Here we determined normal cardiac and aortic reference ranges in healthy Singaporean Chinese and investigated how these data might affect clinical interpretation of CMR scans. Methods In 180 healthy Singaporean Chinese (20 to 69 years old; males, n = 91), comprehensive cardiac assessment was performed using the steady state free precision technique (3T Ingenia, Philips) and images were analysed by two independent observers (CMR42, Circle Cardiovascular Imaging). Measurements were internally validated using standardized approaches: left ventricular mass (LVM) was measured in diastole and systole (with and without papillary muscles) and stroke volumes were compared in both ventricles. All reference ranges were stratified by sex and age; and "indeterminate/borderline" regions were defined statistically at the limits of the normal reference ranges. Results were compared with clinical measurements reported in the same individuals. Results LVM was equivalent in both phases (mean difference 3.0 ± 2.5 g;P = 0.22) and stroke volumes were not significantly different in the left and right ventricles (P = 0.91). Compared to females, males had larger left and right ventricular volumes (P < 0.001 for all). Indexed LVM was significantly higher in males compared to females (50 ± 7 versus 38 ± 5 g/m2, respectively;P < 0.001). Overall, papillary muscles accounted for only 2 % of the total LVM. Indexed atrial sizes and aortic root dimensions were similar between males and females (P > 0.05 for all measures). In both sexes, age correlated negatively with left and right ventricular volumes; and positively with aortic sinus and sinotubular junction diameters (P < 0.0001 for all). There was excellent agreement in indexed stroke volumes in the left and right ventricles (0.1±5.7mL/m2, 0.7±6.2 mL/m2, respectively), LVM (0.6±6.4g/m2 ), atrial sizes and aortic root dimensions between values reported in clinical reports and our measured reference ranges. Conclusions Comprehensive sex and age-corrected CMR reference ranges at 3T have been established in Singaporean Chinese. This is an important step for clinical practice and research studies of the heart and aorta in Asia.